Performance of HPV genotyping and GYPC methylation as a triage strategy for HPV-positive women with normal or minimal cytological findings - Saiping Mao; Xing Fan; Xing Fan; Li Yang; Hongtao Li; Dandan Liu; Xiaoli He; Xiaoli Wang; Fang Yu (Frontiers in Medicine)
ObjectiveHigh-risk human papillomavirus (HR-HPV) screening has increased colposcopy referrals, particularly for women with HR-HPV positivity but no intraepithelial lesion or malignancy (NILM) and those with atypical squamous cells of undetermined significance (ASC-US). A fraction of low-grade squamous intraepithelial lesions (LSILs) is associated with cervical intraepithelial neoplasia grade 2 or worse (CIN2+) during diagnosis. This study evaluated the ability of GYPC methylation (GYPCm) to distinguish between <CIN2 and CIN2 + in HPV-positive women with NILM, ASC-US, and LSIL cytology. It also assessed the absolute CIN2+/CIN3 + risk of the triage strategies GYPCm, HPV genotyping, and their combination and compared the clinical performance of each triage strategy.MethodsTo improve cervical screening efficiency, risk stratification based on HPV genotyping and GYPCm was used as a triage strategy.ResultsGYPCm distinguished between <CIN2 and CIN2 + with an area under the receiver operating characteristic curve (AUC) of 0.828. The CIN2 + risk for GYPCm (+) was 36.2%, while that for GYPCm (−) was 2.3%. HPV16/18 combined GYPCm, (+) and (+), (−) and (+) with absolute CIN2 + risk was 41.2 and 35.1%, respectively, whereas (+) and (−), (−) and (−), absolute CIN2 + risk was 6.0 and 1.5%, respectively. Colposcopy referral rates for HPV16/18 or GYPCm and HPV16/18 or ASC-US+ were 35.6 and 79.2%, respectively, with concordant sensitivities (90.2% vs. 87.8%, p > 0.999) and significant differences in specificity (70.5% vs. 21.8%, p < 0.001). The HPV16/18 or GYPCm triage strategy required the least number of referrals to detect a CIN2 + at 3.9 (3.3–4.6).ConclusionHPV16/18 or GYPCm as a triage tool in HPV-positive women with NILM, ASC-US, and LSIL cytology significantly reduced colposcopy referrals while maintaining sensitivity similar to that of HPV16/18 or ASC-US+.